Practice‐based Research Network Research Good Practices (PRGPs): Summary of Recommendations. Issue 6 (22nd August 2015) - Dolor, Rowena J.; Campbell‐Voytal, Kimberly; Daly, Jeanette; Nagykaldi, Zsolt J.; O'Beirne, Maeve; Sterling, Pamela; Fagnan, Lyle J.; Levy, Barcey; Michaels, LeAnn; Louks, Hannah A.; Smith, Paul; Aspy, Cheryl B.; et al.
Abstract: Introduction: Practice‐based research networks (PBRNs) conduct research in community settings, which poses quality control challenges to the integrity of research, such as study implementation and data collection. A foundation for improving research processes within PBRNs is needed to ensure research integrity. Methods: Network directors and coordinators from seven U.S.‐based PBRNs worked with a professional team facilitator during semiannual in‐person meetings and monthly conference calls to produce content for a compendium of recommended research practices specific to the context of PBRNs. Participants were assigned to contribute content congruent with their expertise. Feedback on the draft document was obtained from attendees at the preconference workshop at the annual PBRN meeting in 2013. A revised document was circulated to additional PBRN peers prior to finalization. Results: The PBRN Research Good Practices (PRGPs) document is organized into four chapters: (1) Building PBRN Infrastructure; (2) Study Development and Implementation; (3) Data Management, and (4) Dissemination Policies. Each chapter contains an introduction, detailed procedures for each section, and example resources with information links. Conclusion: The PRGPs is a PBRN‐specific resource to facilitate PBRN management and staff training, to promote adherence to study protocols, and to increase validity and generalizability of study findings.